Nursing staff's Understanding about risk factors for musculoskeletal disorders associated with carriage of patients in educational centers of Kermanshah University of Medical Sciences in 2017 - Vahid Hatami garosi; mohamadreza zareii; mansoreh farahani; hamid haghani (Kurdistan University of Medical Sciences, 2017)
Abstract Background & Aim: Musculoskeletal disorders associated with patient transport are one of the most common occupational diseases in nursing staff. The objective of this study was to determine the understanding of nursing staffs about the risk factors of musculoskeletal disorders associated with carriage of patients in educational centers of Kermanshah University of Medical Sciences in 2017. Methods & Materials: In this descriptive cross-sectional study, 270 nursing staff were studied in 2017. The sampling method was proportional in this stratified study. In order to assess nurses' understanding about the risk factors that cause the development of musculoskeletal disorders, a 17-item questionnaire, which was based on a survey of Nigerian nurses working on musculoskeletal disorders, was used. After entering the data in SPSS 21, descriptive and inferential statistics such as Chi-square, independent t-test, ANOVA and Pearson correlation coefficient were used to achieve the goals and to answer the research questions. Results: The average working hours per week was 14.44±13.17 hours. 53.7% of nursing staff had self-treatment due to work-related problems. The most painful organ of the nursing staff was the lower back (42.8%) and neck (20.4%). The understanding of the majority (85.6%) of nursing staff was minimal in relation to the risk factors for musculoskeletal disorders associated with carrying the patient. Work experience (P=0.031), work situation in the last 12 months (P=0.40) and job position (P=0.005) had a significant relationship with understanding. Conclusion: According to the results of this study, considering the musculoskeletal disorders related to patients’ carriage among the nursing staff, education and improvement of existing conditions were necessary in order to reduce and prevent these disorders.